Environmental pressures shape regional patterns of genetic diversity and ancestry in cotton landraces - Shrestha, Avinash; Gudino, Maximus A.; Angeles-Shim, Rosalyn B. (Frontiers in Plant Science, 2025)
Upland cotton has undergone extensive domestication and breeding, leading to substantial genetic improvement but also a pronounced narrowing of its genetic base. To better characterize and leverage the diversity preserved in traditional gene pools, we examined the population structure, phylogenetic relationships, and genomic signatures of selection in a globally sourced panel of cotton landraces and elite cultivars. STRUCTURE and neighbor-joining analyses based on whole-genome SNP genotyping identified four ancestral populations divided into nine major clusters. The landrace accessions formed deep, regionally coherent lineages characterized by high heterozygosity and an abundance of private alleles. Consistent with these patterns, Nei’s genetic distance and pairwise FST estimates revealed strong divergence between Mesoamerican and Central American landraces relative to modern breeding lines. Flowering time, a key adaptive trait, was strongly associated with genetic clusters, with photoperiod-sensitive genotypes primarily originating from highland and tropical regions. Genome-wide scans of Tajima’s D further differentiated landraces from cultivars, revealing signatures of balancing selection and ancestral polymorphism in the landraces, and selective sweeps in cultivated accessions. Notably, flowering-related genes on chromosomes D05 and A05 were located in regions exhibiting contrasting Tajima’s D values between the two gene pools. These findings demonstrate that cotton landraces have retained valuable genomic regions lost from modern cultivars through domestication and decades of intensive improvement. As such, they represent an important reservoir for enhancing resilience, adaptation, and fiber traits in modern cotton. Collectively, our results provide a high-resolution framework for targeted pre-breeding and conservation initiatives, underscoring the untapped potential of landraces in broadening the genetic base of cultivated G. hirsutum.